Assembly and Characterizations of Bifunctional Fluorescent and Magnetic Microneedles With One Decade Length Tunability. (10th July 2017) - Lugagne, Jean‐Baptiste; Brackx, Gwennhaël; Seyrek, Emek; Nowak, Sophie; Sivry, Yann; Vitorazi, Leticia; Berret, Jean‐François; Hersen, Pascal; Charron, Gaëlle
Abstract : This report presents the fabrication of bifunctional magnetic and fluorescent microneedles (µNDs) made of a ternary mixture of magnetic nanoparticles (NPs), quantum dots (QDs), and polyelectrolyte. The assembly relies on the electrostatic complexation of negatively charged NPs with positively charged polymer strands and is controlled by the charge ratio between the nanoparticle building blocks and the polymer mortar. The resulting 1D objects can be actuated using an external magnetic field and can be imaged using fluorescence microscopy, thanks to the fluorescent and superparamagnetic properties inherited from their NP constituents. Using a combination of core and surface characterizations and a state‐of‐the‐art image analysis algorithm, the dependence of the brightness and length on the ternary composition is thoroughly investigated. In particular, statistics on hundreds of µNDs with a range of compositions show that the µNDs have a log‐lormal length distribution and that their mean length can be robustly tuned in the 5–50 µm range to match the relevant length scales of various applications in micromixing, bioassays or biomechanics. Abstract : Bifunctional microneedles are assembled from magnetic nanoparticles, quantum dots, and polyelectrolyte using a straightforward protocol . The microneedles are both fluorescent and responsive under an external magnetic field and their mean length can be tuned from 5 to 50 µm by playing on the starting composition to match the needs of several applications.